Top 20 of the most dangerous alien plant species according to iNaturalist and GBIF electronic resources (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Question: Which alien invasive plant species are the most dangerous in Ukraine according to data from electronic resources? Locations: Ukraine. Methods:, critical analysis of the literature sources and electronic resources Nomenclature: Euro+Med Plantbase (https://www.europlusmed.org/). Results: Based on a critical analysis of the literary sources, a list of 69 species that can potentially be considered dangerous invasive in Ukraine has been compiled. For each of these species, the number of occurrences in Ukraine was determined based on data from the GBIF and iNaturalist electronic resources. Comparison of the data obtained by frequency of occurrence allowed us to select 20 species with the largest number of localities in Ukraine, according to GBIF and iNaturalist. The first five positions in both lists belong to the same species, although their order in the top 5 is slightly different. According to the analysis, the most dangerous invasive alien species in the flora of Ukraine are Acer negundo, Erigeron canadensis, Erigeron annuus, Ambrosia artemisiifolia, and Robinia pseudoacacia. Conclusions: The analysis of electronic resources as an additional criterion along with other criteria (ecological, phytocoenotic, dynamic, etc.) in determining the degree of invasiveness of alien species gives fairly objective outcomes since the use of citizen science resources provides more or less uniform coverage of the country's territory and is not related to research plans, which often affect the uniformity of the distribution of available data. In addition, the vast majority of data on these resources have been collected over the past five years, i.e., they reflect the current distribution of these species, not their past distribution, which is reflected in literature and archival sources and may well differ from the current state.
Keywords: alien plants, invasiveness criteria, phytoinvasions, species distribution, GBIF, iNaturalist, filtered data.